2023
DOI: 10.1093/ehjacc/zuad066
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed mechanical aspiration thrombectomy in a real-world pulmonary embolism population: a multicenter registry

Abstract: Background High- (HR) and intermediate-high risk (IHR) pulmonary embolisms (PEs) are related to high early mortality and long-term sequelae. We aimed to describe clinical outcomes and adverse events in IHR and HR PE treated with catheter-directed mechanical thrombectomy (CDMT) in a real-world population. Methods This study is a multicenter, prospective registry enrolling 110 PE patients treated with CDMT between 2019 and 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…No patients required a blood transfusion due to aspiration. These results are in line with other reports with the use of Penumbra 8F catheter with estimated overall blood loss < 400 ml [20,30]. Similar results were obtained when comparing large-bore CDMT with CDL [37].…”
Section: Safety Outcomessupporting
confidence: 91%
See 1 more Smart Citation
“…No patients required a blood transfusion due to aspiration. These results are in line with other reports with the use of Penumbra 8F catheter with estimated overall blood loss < 400 ml [20,30]. Similar results were obtained when comparing large-bore CDMT with CDL [37].…”
Section: Safety Outcomessupporting
confidence: 91%
“…In the EXTRACT-PE trial, the 30-day mortality was 2.5% [20]. Advanced oncological disease is reported to be the most common cause of death in the posthospital period [30][31][32]. A recent study indicated three times higher mortality during 12 months after PE diagnosis as compared to non-oncological patients [33].…”
Section: Safety Outcomesmentioning
confidence: 99%
“…The wide diameter of thrombectomy devices allow to effectively extract large organized and adherent emboli through aspiration. Clinical single-arm studies completed on these devices have shown a lower major bleeding incidence and mortality, significant reduction of RV dysfunction and PA pressure and lower mean stay in intensive care units, strengthening their role in determined clinical scenarios and creating opportunities for RCT's [27][28][29][30][31][32][33][34]. This review will discuss the most studied products available.…”
Section: Mechanical Thrombectomymentioning
confidence: 99%
“…Recently, a new Lightning 12, intelligent computer-assisted vacuum aspiration system (Penumbra, Alameda, CA, US) has been introduced, which is thought to more efficiently regulate aspiration, and reduce blood loss in comparison to the previous generation device (Indigo CAT8) [4][5][6]. This study aims to evaluate the outcomes of the Lightning 12 aspiration system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the 12F catheter's flexibility advantageously improves maneuvers within tortuous vessels and enlarged right heart ventricles. A larger diameter, improved catheter design, and an intelligent control unit allow for the more adequate removal of thrombi from both pulmonary arteries without increasing periprocedural blood loss compared to the previous generation of the device (Indigo CAT8 device) [5,[9][10][11]. Using larger-bore catheters and sheaths seems feasible and effective.…”
mentioning
confidence: 99%